درجة تطبيق استراتيجية التمكين في تنمية رأس المال الفكري في وزارة التربية والتعليم بسلطنة عمان : "دراسة وصفية تحليلية" - غسيني، محمد سالم سليمان (Kulliyah of Education, International Islamic University Malaysia, 2020)
In light of the importance of applying the empowerment strategy in developing intellectual capital, the present study aims to explore the degree of implementing empowerment strategy in developing intellectual capital (human, structural, and relations) in Ministry of Education Sultanate of Oman. In addition, it examines any statistically significant differences in implementing empowerment strategy in developing intellectual capital based on respondents' gender, qualification, job title and working experience. This quantitative study employed the descriptive research design as it is the suitable research design to fulfil its objectives. 292 questionnaires were randomly distributed among the selected employees (directors, assistant directors and heads of department) from Ministry's departments as well as the directorates- General of Education in four governorates (Muscat, Dhahirah, Ash Sharqiyah South and Dakhiliyah). The questionnaire used in this study included two main sections. Section A is about respondents' demographics while section B is about the implementation of empowerment strategy in developing intellectual capital (human, structural, and relations). The Descriptive statistics using SPSS software was used to examine the current degree of implementing empowerment strategy in developing intellectual capital (human, structural, and relations). Inferential statistics was also employed to investigate if there were any statistically significant differences in implementing empowerment strategy in developing intellectual capital based on respondents' gender, qualification, job title and working experience. The findings of this research showed that the degree of implementing empowerment strategy in developing intellectual capital (human, structural, and relations) is moderate. Furthermore, the results indicated that there are no statistically significant differences in implementing empowerment strategy in developing intellectual capital according to respondents' gender, qualification and job title. However, statistically significant difference was found based on respondents' working experience in favour of those who had less than 23years working experience. This study concluded with recommendations regarding implementation of empowerment strategy in developing intellectual capital in the Ministry of Education-Sultanate of Oman.